Bats from Fazenda Intervales, Southeastern Brazil: species account and comparison between different sampling methods - Portfors, Christine V.; Fenton, M. Brock; Aguiar, Ludmilla M. de S.; Baumgarten, Julio E.; Vonhof, Maarten J.; Bouchard, Sylvie; Faria, Deborah M. de; Pedro, Wagner André [UNESP]; Rauntenbach, Naas I. L.; Zortea, Marlon (Sociedade Brasileira de Zoologia, 2000)
Assessing the composition of an area's bat fauna is typically accomplished by using captures or by monitoring echolocation calls with bat detectors. The two methods may not provide the same data regarding species composition. Mist nets and harp traps may be biased towards sampling low flying species, and bat detectors biased towards detecting high intensity echolocators. A comparison of the bat fauna of Fazenda Intervales, southeastern Brazil, as revealed by mist nets and harp trap captures, checking roosts and by monitoring echolocation calls of flying bats illustrates this point. A total of 17 species of bats was sampled. Fourteen bat species were captured and the echolocation calls of 12 species were recorded, three of them not revealed by mist nets or harp traps. The different sampling methods provided different pictures of the bat fauna. Phyllostomid bats dominated the catches in mist nets, but in the field their echolocation calls were never detected. No single sampling approach provided a complete assessment of the bat fauna in the study area. In general, bats producing low intensity echolocation calls, such as phyllostomids, are more easily assessed by netting, and bats producing high intensity echolocation calls are better surveyed by bat detectors. The results demonstrate that a combined and varied approach to sampling is required for a complete assessment of the bat fauna of an area.
Keywords: Atlantic rain forest; bats; bat detector; chiroptera; diversity; echolocation; sampling methods; southeastern Brazil